Social adaptation among international students in Malaysia: the uncertainty reduction perspective - Ssemuddu, Imran; Tengku Mohd Azzman, Tengku Siti Aisha (University Putra Malaysia, 2021)
Social adaptation can be a challenging and arduous process for any international students. However, having strong interpersonal connections and being able to speak a local language can influence how an international student adapts to their new country. From the perspective of uncertainty reduction theory (URT) by Berger and Calabrese (1975), adaptation can be increased if the individual is motivated to reduce uncertainty by widening their social interactions with host nationals. More current studies on cross-cultural adaptation are looking into how new media and communication technology facilitate cultural adaptation among immigrants and sojourners. Accordingly, this study aims to examinethe role of social support, uncertainty adaptability and social media use in influencing social adaptation process among international students from a Malaysian public university. Using a cross-sectional survey, questionnaires was distributed among international students from five different faculties in a public Malaysian university (N = 385). Overall, results from the study established the importance of having strong social support and establishing communication with family and friends through social media use in order to navigate the process of social adaptation in Malaysia. Also, findings provide some support for URT; uncertainty adaptability partially mediated the relationship between social media use and social adaptation. The implications of these findings on URT, as well as the role of social media as a cross-cultural adaptation tool will be discussed.